2022
DOI: 10.1038/s41598-022-06522-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of cultured white soft cheese on the histopathological changes in the kidneys and liver of albino rats

Abstract: Three different types of lactic acid bacteria (Lactobacillus helveticus, Lactobacillus rhamnosus and Streptococcus thermophilus S3855) were used to manufacture white soft cheese. The resultant white soft cheeses were pickled for 28 days at refrigerator temperatures and were fed to the experimental rats. The chemical and microbiological analyses of white soft cheese were conducted at different storage periods (fresh, 7 days, 14 days, 21 days, and 28 days). The pH values and protein content of white soft cheese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Data (mean ± standard deviation) were compared between groups using a t -test performed with the Statistical Program for Social Science version 2. Histopathological scoring data were compared using one-way analysis of variance (ANOVA) with Tukey’s post hoc multiple comparison test with GraphPad Prism, version 5 (San Diego, California, CA, USA) [ 53 ]. A p -value < 0.05 was considered to indicate a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…Data (mean ± standard deviation) were compared between groups using a t -test performed with the Statistical Program for Social Science version 2. Histopathological scoring data were compared using one-way analysis of variance (ANOVA) with Tukey’s post hoc multiple comparison test with GraphPad Prism, version 5 (San Diego, California, CA, USA) [ 53 ]. A p -value < 0.05 was considered to indicate a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…The histopathological measurements from the experimental groups were stated as mean ± standard deviation (SD) and estimated using Version 5 of GraphPad Prism (San Diego, California, USA) for analyzing data using the one-way ANOVA and Tukey's post hoc multiple-comparisons tests; the statistical significance was considered at a P-value of <0.05 (52,53). As regards the serum biochemical parameters, data were collected and then analyzed using SPSS.28 software.…”
Section: Statistical Analysismentioning
confidence: 99%
“…Doublecortin-like kinase 1 protein (DCLK1) marks differentiated tuft cells in the small intestine and colon epithelium [11]. Cluster cell-derived IL-25 helps drive the feed-forward Tuft-ILC2 signaling pathway [12], in which ILC2 is activated to produce IL-5 and IL-13, thereby promoting type 2 inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above results, it was found that IL-25 might affect the expression of related factors in the Tuft-IL-25-ILC2 pathway in the ES antigen-stimulated mouse small intestine. Doublecortin-like kinase 1 protein (DCLK1) marks differentiated tuft cells in the small intestine and colon epithelium [11]. Cluster cell-derived IL-25 helps drive the feed-forward Tuft-ILC2 signaling pathway [12], in which ILC2 is activated to produce IL-5 and IL-13, thereby promoting type 2 inflammation.…”
Section: Il-25-ilc2 Pathwaymentioning
confidence: 99%